2005
DOI: 10.1002/mnfr.200500015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibres as “prebiotics”: Implications for colorectal cancer

Abstract: A "prebiotic" is a nondigestible food ingredient whose beneficial effects on the host result from the selective stimulation of growth and/or activity of members of the bacterial community that inhabits the human bowel (the gut microbiota). Although much of the prebiotic literature focuses on nondigestible oligosaccharides, such as oligofructose, most dietary fibres that are fermentable carbohydrates could be considered as prebiotics. Early studies suggested that colonic bacteria were risk factors for colon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 111 publications
(78 reference statements)
1
93
0
Order By: Relevance
“…There have been several studies on the use of prebiotics in cancer prevention mainly focusing on animal models, but the "dietary fiber hypothesis" for protection against colorectal cancer was advanced by Burkitt (1969) based on epidemiological evidence supporting a relationship between diet and colon health. These findings showed lower rates of colorectal cancer in Africa compared to industrialized Western countries, where traditional diets consisted of high amounts of unrefined fiber and high intakes of refined carbohydrates, respectively (Manning and Gibson 2004;Lim et al 2005a). …”
Section: Protection Against Colon Cancermentioning
confidence: 88%
“…There have been several studies on the use of prebiotics in cancer prevention mainly focusing on animal models, but the "dietary fiber hypothesis" for protection against colorectal cancer was advanced by Burkitt (1969) based on epidemiological evidence supporting a relationship between diet and colon health. These findings showed lower rates of colorectal cancer in Africa compared to industrialized Western countries, where traditional diets consisted of high amounts of unrefined fiber and high intakes of refined carbohydrates, respectively (Manning and Gibson 2004;Lim et al 2005a). …”
Section: Protection Against Colon Cancermentioning
confidence: 88%
“…Prebiotics are defined as, "nondigestible food ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of one, or a limited number of bacteria in the colon, thus improving host health". 53 Common prebiotics include inulin, fructooligosaccharide, lactulose, and resistant starch. 53 Dietary fibre has also been shown to convey a prebiotic effect which has been linked to the reduction of CRC.…”
Section: Prebiotics and Crcmentioning
confidence: 99%
“…53 Common prebiotics include inulin, fructooligosaccharide, lactulose, and resistant starch. 53 Dietary fibre has also been shown to convey a prebiotic effect which has been linked to the reduction of CRC. 54 A meta-analysis by Friedenreich et al, 54 concluded that consumption of over 27 g of fibre per day resulted in a 50% reduction in CRC compared to consumption of less than 11 g. Young et al 43 have comprehensively reviewed the evidence for the potential benefits of dietary fibre in the reduction of CRC.…”
Section: Prebiotics and Crcmentioning
confidence: 99%
“…Prebiotics are produced either by extraction from natural sources or by chemical synthesis [59] [60]. Most common prebiotics are inulin, fructooligosaccharide, lactulose, and resistant starch [61] [62].…”
Section: Prebioticsmentioning
confidence: 99%